CONVERGENCE STUDIES OF MASS TRANSPORT IN DISKS WITH GRAVITATIONAL INSTABILITIES. II. THE RADIATIVE COOLING CASE - Steiman-Cameron, Thomas Y.; Durisen, Richard H.; Boley, Aaron C.; Michael, Scott; McConnell, Caitlin R. (The Astrophysical journal, 2013)
We conduct a convergence study of a protoplanetary disk subject to gravitational instabilities (GIs) at a time of approximate balance between heating produced by the GIs and radiative cooling governed by realistic dust opacities. We examine cooling times, characterize Gl-driven spiral waves and their resultant gravitational torques, and evaluate how accurately mass transport can be represented by an alpha -disk formulation. Four simulations, identical except for azimuthal resolution, are conducted with a grid-based three-dimensional hydrodynamics code. There are two regions in which behaviors differ as resolution increases. The inner region, which contains 75% of the disk mass and is optically thick, has long cooling times and is well converged in terms of various measures of structure and mass transport for the three highest resolutions. The longest cooling times coincide with radii where the Toomre Q has its minimum value. Torques are dominated in this region by two- and three-armed spirals. The effective alpha arising from gravitational stresses is typically a few x 10 super(-3) and is only roughly consistent with local balance of heating and cooling when time-averaged over many dynamic times and a wide range of radii. On the other hand, the outer disk region, which is mostly optically thin, has relatively short cooling times and does not show convergence as resolution increases. Treatment of unstable disks with optical depths near unity with realistic radiative transport is a difficult numerical problem requiring further study. We discuss possible implications of our results for numerical convergence of fragmentation criteria in disk simulations.